2023
DOI: 10.1186/s12954-023-00875-x
|View full text |Cite
|
Sign up to set email alerts
|

The utilization and delivery of safer smoking practices and services: a narrative synthesis of the literature

Abigail Tapper,
Catherine Ahern,
Zoe Graveline-Long
et al.

Abstract: Background Providing sterile drug smoking materials to people who use drugs can prevent the acquisition of infectious diseases and reduce overdose risk. However, there is a lack of understanding of how these practices are being implemented and received by people who use drugs globally. Methods A systematic review of safer smoking practices was conducted by searching PubMed, PsycInfo, Embase for relevant peer-reviewed, English-language publications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Prior research has shown providing safer smoking pipes can lead to reductions in the frequency of injections and risky smoking practices (e.g. pipe sharing, using broken pipes), as well as improved health outcomes among those who smoke drugs, such as fewer burns and cuts (Leonard et al, 2008; Bridge, 2010; Stöver & Schäffer, 2014; Frankeberger et al, 2019; Dunleavy et al, 2021; Fitzpatrick et al, 2022; Tapper et al, 2023). Given SSPs are trusted by PWUD (MacNeil & Pauly, 2011), they are ideal programs for distributing safer smoking supplies.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has shown providing safer smoking pipes can lead to reductions in the frequency of injections and risky smoking practices (e.g. pipe sharing, using broken pipes), as well as improved health outcomes among those who smoke drugs, such as fewer burns and cuts (Leonard et al, 2008; Bridge, 2010; Stöver & Schäffer, 2014; Frankeberger et al, 2019; Dunleavy et al, 2021; Fitzpatrick et al, 2022; Tapper et al, 2023). Given SSPs are trusted by PWUD (MacNeil & Pauly, 2011), they are ideal programs for distributing safer smoking supplies.…”
Section: Introductionmentioning
confidence: 99%